Flow-Mediated Susceptibility and Molecular Response of Cerebral Endothelia to SARS-CoV-2 Infection. Issue 1 (January 2021) - Kaneko, Naoki; Satta, Sandro; Komuro, Yutaro; Muthukrishnan, Sree Deepthi; Kakarla, Visesha; Guo, Lea; An, Jennifer; Elahi, Fanny; Kornblum, Harley I.; Liebeskind, David S.; Hsiai, Tzung; Hinman, Jason D.
Abstract : Background and Purpose: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection is associated with an increased rate of cerebrovascular events including ischemic stroke and intracerebral hemorrhage. The mechanisms underlying cerebral endothelial susceptibility and response to SARS-CoV-2 are unknown yet critical to understanding the association of SARS-CoV-2 infection with cerebrovascular events. Methods: Endothelial cells were isolated from human brain and analyzed by RNA sequencing. Human umbilical vein and human brain microvascular cells were used in both monolayer culture and endothelialized within a 3-dimensional printed vascular model of the middle cerebral artery. Gene expression levels were measured by quantitative polymerase chain reaction and direct RNA hybridization. Recombinant SARS-CoV-2 S protein and S protein–containing liposomes were used to measure endothelial binding by immunocytochemistry. Results: ACE2 (angiotensin-converting enzyme-2) mRNA levels were low in human brain and monolayer endothelial cell culture. Within the 3-dimensional printed vascular model, ACE2 gene expression and protein levels were progressively increased by vessel size and flow rates. SARS-CoV-2 S protein–containing liposomes were detected in human umbilical vein endothelial cells and human brain microvascular endothelial cells in 3-dimensional middle cerebral artery models but not in monolayer culture consistent with flow dependency of ACE2 expression. Binding of SARS-CoV-2 S protein triggered 83 unique genes in human brain endothelial cells including upregulation of complement component C3. Conclusions: Brain endothelial cells are susceptible to direct SARS-CoV-2 infection through flow-dependent expression of ACE2. Viral S protein binding triggers a unique gene expression profile in brain endothelia that may explain the association of SARS-CoV-2 infection with cerebrovascular events. Abstract : Supplemental Digital Content is available in the text.